2012
DOI: 10.1126/science.1215343
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Experience and Attrition for Novice High-School Science and Mathematics Teachers

Abstract: Because of the current high proportion of novice high-school teachers, many students' mastery of science and mathematics depends on the effectiveness of early-career teachers. In this study, which used value-added models to analyze high-school teachers' effectiveness in raising test scores on 1.05 million end-of-course exams, we found that the effectiveness of high-school science and mathematics teachers increased substantially with experience but exhibited diminishing rates of return by their fourth year; tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 18 publications
2
59
0
Order By: Relevance
“…On average, beginning teachers' performance statistically significantly improved over the four years of study, while performance of teachers with six or more years of experience remained fairly stable. Our results are consistent with findings from studies that examine teacher learning, which have found that improvements in teaching are most notable in the first few years in the classroom (Henry, Fortner, & Bastian, 2012). If policy seeks to address stable, average performance, one implication of our findings might be that VAEs are best used only after a teacher has taught for five years.…”
Section: Discussionsupporting
confidence: 82%
“…On average, beginning teachers' performance statistically significantly improved over the four years of study, while performance of teachers with six or more years of experience remained fairly stable. Our results are consistent with findings from studies that examine teacher learning, which have found that improvements in teaching are most notable in the first few years in the classroom (Henry, Fortner, & Bastian, 2012). If policy seeks to address stable, average performance, one implication of our findings might be that VAEs are best used only after a teacher has taught for five years.…”
Section: Discussionsupporting
confidence: 82%
“…schools face in other parts of their lives, and exacerbates staff recruitment challenges. Moreover, departing teachers are disproportionately replaced with novices, who on average are less effective than their more experienced peers (see Henry et al 2012 ;Kane et al 2006 ;Papay and Kraft Forthcoming ). Once these teachers obtain a little experience and skill, they also often depart (to be replaced with a new round of novices), creating a pattern of reshuffl ing of teachers from poor to not-poor schools, high-minority to low-minority schools, and urban to suburban schools (Ingersoll et al 2014 ).…”
Section: Unequal Resourcesmentioning
confidence: 99%
“…Initially, we did expect that experienced teachers' conceptions would be more developed, since they had more time to gain experience and knowledge than their less experienced counterparts. Previous studies show that beginning teachers improve n their instruction and knowledge over time (Henry, Fortner, & Bastian, 2012). Yet, the lack of professional development on NOS for practicing teachers may explain why there was virtually no difference in conceptions of NOS between the novice teachers and the experienced teachers.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for choosing the dividing line for experience in teaching at 0-5 versus 6 or more is that teachers with less than 6 years of teaching experience are considered 'beginning teachers' (Luft et al, 2011). Teachers in this phase of their career are still acclimating to their new role as science and mathematics teachers and are more moldable in their practices when compared to their more experienced peers (Henry, Fortner, & Bastian, 2012;Luft, 2001).…”
Section: Situatedmentioning
confidence: 99%